Decrypting the Central Mystery of Quantum Mathematics:: Part 3. A Non-Einstein, non-QM View of Bell Test Experiments - Boyd, Jeffrey (JOURNAL OF ADVANCES IN MATHEMATICS, 2019)
The fact that loophole-free Bell test experiments have proved Einstein’s local realism wrong, does not prove that the quantum mechanical (QM) model is correct, because the Theory of Elementary Waves (TEW) Axioms can also explain the Bell test experiments. Bi-Rays are a pair of coaxial elementary rays traveling at the speed of light in countervailing directions. In a Bell test experiment a Bi-Ray stretches from Alice’s equipment, through the fiberoptic cable, across the 2-photon source, through more fiberoptic cable, to Bob’s equipment. A pair of entangled photons is born into that Bi-Ray. Each photon follows the same Bi-Ray in opposite directions. This model produces the same Bell test results found by QM. According to QM this would be classified as a “non-local” model, so it is no surprise that it can explain the Bell test results. But it is a different model than QM. TEW supports a more realistic view of Nature, based on better Axioms. Although QM can explain quantum experiments, it requires that you believe the quantum world is weird. TEW Axioms explain the quantum world in a way that is more intuitively similar to the world of everyday experience.